Treatment of metastatic ALK-positive non-small cell lung cancer: indirect comparison of different ALK inhibitors using reconstructed patient data - Damuzzo, Vera; Gasperoni, Lorenzo; Del Bono, Luna; Ossato, Andrea; Inno, Alessandro; Messori, Andrea (Frontiers in Oncology, 2025)
IntroductionAnaplastic lymphoma kinase (ALK) inhibitors (ALKi) are the standard treatment for metastatic, ALK-positive non-small cell lung cancer (NSCLC). Second- and third-generation ALKi, including alectinib, brigatinib, ensartinib, envonalkib, and lorlatinib, have shown better efficacy than crizotinib. However, due to the lack of direct head-to-head comparisons among these agents, the optimal treatment for metastatic ALK-positive NSCLC remains unclear.MethodsThis study used the IPDfromKM (Individual Patient Data from Kaplan-Meier) method to reconstruct patient-level data from Kaplan-Meier curves of seven randomized phase III trials, involving a total of 3,850 patients. Crizotinib arms were pooled as the common comparator. Progression-free survival (PFS) was the primary endpoint, assessed using Cox proportional hazards models and restricted mean survival time (RMST). Subgroup analyses focused on patients with baseline central nervous system (CNS) metastases.ResultsAll ALKi significantly improved PFS compared to crizotinib. Lorlatinib showed the most meaningful improvement, with the greatest benefit in both overall PFS (HR=0.28; 95% CI 0.21-0.38) and CNS PFS (HR=0.09; 95% CI 0.04-0.2). In direct comparisons, lorlatinib outperformed brigatinib (HR=0.59; 95% CI 0.39-0.87) and envonalkib (HR=0.52; 95% CI 0.35-0.77) in terms of PFS. While lorlatinib also showed improved PFS compared to alectinib (HR=0.72; 95% CI 0.50–1.04) and ensartinib (HR=0.73; 95% CI 0.48–1.10), these differences were not statistically significant. Lorlatinib demonstrated the greatest benefit in PFS among patients with baseline CNS metastases.ConclusionIn this indirect comparison using reconstructed patient data, lorlatinib emerged as the most effective ALKi, showed the most favorable HR for PFS compared to the other ALKi, although it did not reach statistical significance versus alectinib and ensartinib. Additionally, lorlatinib showed the highest efficacy in the control of CNS progression.